2010
DOI: 10.1136/ard.2009.119966
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide dismutase downregulation in osteoarthritis progression and end-stage disease

Abstract: Objective-Oxidative stress is proposed as an important factor in osteoarthritis (OA). We therefore investigated the expression of the three superoxide dismutase (SOD) antioxidant enzymes in OA.Methods-SOD expression was determined by real-time polymerase chain reaction and immunohistochemistry using human femoral head cartilage. SOD2 expression in Dunkin Hartley guinea pig knee articular cartilage was determined by immunohistochemistry. The DNA methylation status of the SOD2 promoter was determined using bisul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
166
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 211 publications
(188 citation statements)
references
References 42 publications
17
166
1
2
Order By: Relevance
“…The present study showed that SOD levels can be induced using three different OA in human cartilage (14).…”
Section: Discussionsupporting
confidence: 59%
See 3 more Smart Citations
“…The present study showed that SOD levels can be induced using three different OA in human cartilage (14).…”
Section: Discussionsupporting
confidence: 59%
“…Regardless of the cause, chondrocyte damage results in a vicious cycle of extracellular matrix destruction; which is the hallmark of OA. This degradation of the cartilage matrix results from an imbalance between chondrocyte catabolic and anabolic events (14,15,16).…”
Section: Osteoarthritismentioning
confidence: 99%
See 2 more Smart Citations
“…Modulated proteins found to be up-regulated were procollagen-lysine (PLOD2), which stabilizes the synthesis of collagen type I and II and is involved in the chondrocytic response to TNF-␣-mediated stimuli affecting cartilage homeostasis (16), enolase (ENO1), which increases hypoxia tolerance and is involved in glycolysis (17), Heat shock protein beta-1 (HSPB1), which increases cell survival in changing environ- ments (18), superoxide dismutase (SODm), which destroys free radicals (a reduction in SODm is associated with the earliest stages of osteoarthritis in an animal model) (19), and zyxin (ZYX), which is involved in signaling pathways. Recent research elaborated by our group revealed that overexpression of Lamin A leads to defects in differentiation potential of MSCs.…”
Section: Discussionmentioning
confidence: 99%